OBE-Driven Ideological and Political Education Reform in Event Management: A Case Study of Event Planning and Management - lin, siki (Pacific International Journal, 2025)
Under the National Education Strengthening Strategy, the development of “curriculum-based ideological and political education” in higher education has entered a deepening phase. However, event-related majors face challenges like forced ideological incorporation, weak value guidance in practice, and oversimplified evaluation. Using the provincial demonstration course Event Planning and Management as a case, and based on the OBE (Outcome-Based Education) concept, this study innovatively constructs an HCCR curriculum-based ideological and political education goal system, which includes four dimensions: Humanistic Sentiment (cultivating cultural identity and patriotism), Career Competence (strengthening professional standards and occupational responsibility), Creative Thinking (cultivating innovation awareness and practical wisdom), and Social Responsibility (shaping international perspectives and sustainable development views). In terms of teaching methods, it adopts a combination of PBL project-driven method and case teaching, and conducts ’ideological and political education into practice’ activities through internships at international exhibitions such as the Canton Fair, extending ideological education from the university to the industry. At the same time, a dual evaluation mechanism for teachers and students is established. This study provides a systematic reform plan for the ideological and political education of applied professional courses, ’goal-oriented—diverse methods—dual evaluation’, not only fulfills the requirements of the National Education Strengthening Strategy to "establish an education system guided by ideological and political principles", but also providing an effective path to solve the structural contradictions in the cultivation of talents in the exhibition industry.